Designing a Monitoring System and Optimizing Water Quality in Tilapia Farming Ponds in Phokecik Hamlet Using Ubidots - Efendi, Muhammad Taufik Nur; Sulistiyowati, Indah; Syahrorini, Syamsudduha; Anshory, Izza (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
There are several important factors to increase the success rate of tilapia farming. Among them is the regulation of water quality in the pond, which is still mostly done manually. Therefore, a water quality management tool for Ubidots-based tilapia fish farming ponds is made to facilitate tilapia fish farmers in regulating the quality of pond water automatically. so the importance of water quality management of tilapia fish farming ponds is a follow-up to reduce the failure rate in the cultivation process. The components used in this tool are Esp32 as a microcontroller, ph sensor as a water ph value detector, DS18B20 temperature sensor as water temperature detection and turbidity sensor as a water turbidity value detector, Ultrasonic sensor as a pool water level detector, LCD to display the value detected by the sensor, solenoid valve and water pump that functions to drain and fill the pool water. The conclusion of the results obtained from this device is that the device works well and helps tilapia fish farm owners to monitor and control water quality efficiently, although there are some obstacles such as delays due to internet connections. so maybe in the future it can add a solar cell as a power supply for the automatic control process in this system.